Molecular Characteristics of The Mercury Reductase Gene Pseudomonas putida from The Lebong Gold Mine - Raul Fadillon; Rahma Adelia; Waris Rahman; Gita Panny Nababan; Sipriyadi (Department of Biology, Faculty of Science and Technology, Syarif Hidayatullah State Islami, 2026)
Mercury contamination in Lebong Regency has caused serious impacts on public health and environmental quality. Bacteria living in contaminated environments can adapt and develop resistance to mercury through the presence of the merA gene, which plays an important role in converting mercury into a less toxic form. This study aimed to identify and characterize the merA gene in Pseudomonas putida. Molecular identification was carried out using 16S rDNA gene analysis and the polymerase chain reaction (PCR) technique. The obtained DNA sequences were further analyzed to determine gene similarity and phylogenetic relationships. The results showed that the bacterial isolate shared 99% homology with Pseudomonas putida strain CRSD9. The merA gene was 820 bp in length and encoded a mercury reductase enzyme consisting of 310 amino acids. This gene showed 97.78% homology with previously reported mercury reductase genes and contained two important domains, namely Pyridine Nucleotide-Disulfide Oxidoreductase (Pyr Redox) and FAD-linked domains. These findings indicate that Pseudomonas putida has strong potential as a bioremediation agent for reducing mercury pollution in the environment.